PRE-SERVICE FOREIGN LANGUAGE TEACHER EDUCATION IN THE REPUBLIC OF SERBIA: THE OPINIONS OF FOREIGN LANGUAGE TEACHING METHODOLOGY PROFESSORS (Živi jezici: Journal for Foreign Languages and Literatures, 2025)
According to the current legal regulations of the Republic of Serbia, teachers employed in primary and secondary schools must obtain a certain level of education (MA degree) that meets predefined requirements (30 credits in psychological, pedagogical and teaching methodological subjects). Therefore, we believe that the opinions of university professors who educate the future teaching staff are of vital importance for the quality of foreign language teaching. The primary goal of this paper is to gain insight into the importance and organization of initial teacher education of foreign language teachers from the perspective of university professors engaged in language teaching courses at universities in the Republic of Serbia. Through an online anonymous questionnaire, we investigate professors' points of view regarding the current trends in the initial education of foreign language teachers and their possibility of acquiring  the necessary teaching competencies. The focus of the paper is exclusively on the foreign language teaching methodology courses at universities that educate future foreign language teachers. The foreign languages that are relevant for this research are those taught in primary and secondary schools in the Republic of Serbia, namely English, German, Russian, French, Spanish and Italian. Based on the results of the survey, we analyze the organization of the existing language teaching oriented university courses, as well as the necessity to reconcile them with modern language education policies and planning.
Keywords: language education policy; initial teacher education; foreign languages; foreign language teaching methodology